1977
DOI: 10.1002/bjs.1800640603
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary function in the early postoperative period

Abstract: To the author's knowledge, an intensive investigation of pulmonary function during the first 2 postoperative days has not previously been reported. Consequently, in this study the effect of regional surgery on respiratory function, monitored every 4 h during the first 2 postoperative days, was analyzed. Hypoxaemia was a constant finding in all patients undergoing general anaesthesia. The degree and duration of hypoxaemia and spirometry changes were related to the site of surgical incision. Clinical signs of at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0
2

Year Published

1977
1977
2009
2009

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 17 publications
0
6
0
2
Order By: Relevance
“…Each patient completed a questionnaire based on the respiratory questionnaire of the Medical Research Council (1962) and relevant intra-operative and postoperative factors were noted. The Po, was measured using arterialized capillary blood, which accurately reflects the arterial Po8 (Parfrey et al, 1977). The arterialized capillary blood was collected from the earlobe following local vasodilatation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Each patient completed a questionnaire based on the respiratory questionnaire of the Medical Research Council (1962) and relevant intra-operative and postoperative factors were noted. The Po, was measured using arterialized capillary blood, which accurately reflects the arterial Po8 (Parfrey et al, 1977). The arterialized capillary blood was collected from the earlobe following local vasodilatation.…”
Section: Methodsmentioning
confidence: 99%
“…In a companion paper (Parfrey et al, 1977) we have investigated the pulmonary changes in the early postoperative period following regional surgery and significant decreases in Po, were observed in certain patients. The efficiency and predictability of oxygen therapy in the correction of hypoxaemia following upper abdominal surgery have been discussed by Drummond (1975), who confirmed that oxygen desaturation was relieved by breathing an oxygenenriched mixture, but desaturation developed again when the oxygen was withdrawn.…”
mentioning
confidence: 99%
“…[1][2][3][4][5][6] Pulmonary function testing (PFT) can provide objective, quantitative information on the type, severity, and functional impairment caused by a respiratory disorder. [7][8][9][10][11] Thoracic surgery decreases lung volumes, expiratory flow rates, and oxygenation after surgery as a result of the surgery itself, anesthesia, pain, and immobilization. 1,[11][12][13] In adult studies, thoracic and upper abdominal surgery may reduce lung volumes and flow rates 50% to 75% from their preoperative baseline values.…”
mentioning
confidence: 99%
“…The cause of the hypoxaemia appears to be a combination of factors rather than any single mechanism.3 One factor which has been shown to affect the severity of hypoxaemia is the site of operation.4 5 In this report, upper abdominal incisions are associated with more profound hypoxaemia than incisions in the lower abdomen. Though there have been reports of hypoxaemia after pulmonary resection,' 6 7 there appear to be no published data regarding arterial oxygen levels after thoracotomy for non-cardiopulmonary disease.…”
mentioning
confidence: 71%